Advancing forest-based carbon trading in Nepal: Policy challenges and agroforestry opportunities - Chaudhary, Arbind; Babu, Suresh Chandra (International Food Policy Research Institute, 2025)
Nepal remains among the countries most vulnerable to climate-related disasters. Although several national policy documents have emphasized the urgency of mitigation and adaptation, climate action remains fragmented and significantly underfunded. Nepal’s unique geography—spanning the Himalayas, mid-hills, and Tarai plains—together with recent decentralization reforms offers a favorable context for implementing localized, context-specific solutions to climate threats. However, the lack of consistent policy frameworks, weak institutional mechanisms, limited investment, and fragmented governance across all levels of government continue to impede progress.